Strategies for Utilizing Technology in Learning - Abbas, Azwar; Nurjannah, Asfinatu; Isnaini, Rahma; Eliyana, Ema (Global Synthesis in Education Journal, 2024)
This study investigates the intercultural relationship development of English as a Foreign Language (EFL) students participating in an International Learning Program. Amid travel restrictions, a limited number of students engaged in a cross-border experience in Malaysia and Singapore. Employing a descriptive qualitative approach, the research examines the stages of intercultural relationship development and associated challenges. Twenty eighth-grade students from East Java, Indonesia, comprising an equal distribution of male and female participants, were selected for the study. Through analysis, three distinctive stages emerged in the process of intercultural competence (ICC) development: "trial," involving the exploration of new customs and habits; "enmeshment," focusing on individual character growth in new contexts; and "renegotiation," emphasizing dialogue and reflection on cultural experiences' impacts. Drawing on existing literature, the study proposes strategies for ICC development, including self-awareness, cultural awareness, motivation enhancement, and cultural knowledge acquisition. Additionally, ICC improvement techniques, such as cultural assimilation, comparison methods, and reformulation, were identified as valuable tools for English language instruction.